ANALYSIS OF EXTERNAL FACTORS ON RURAL ECOTOURISM ENTREPRENEURSHIP (CASE STUDY IN BOGOR REGENCY OF WEST JAVA) - Indra Setiawan Purba; Ricky Avenzora; Eva Anggraini; Dudung Darusman (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2023)
The entrepreneurship aspect will determine the success of rural ecotourism development. Rural ecotourism products and services should be attractive and carefully set and packed by entrepreneurs, to attract tourists. This paper studies the external factors that may affect entrepreneurial capacity in rural ecotourism. Research was conducted in four tourist villages in Bogor Regency, namely Ciasihan, Sirnajaya, Watesjaya, and Pabuaran. The 442 respondents were divided into two groups, namely the entrepreneurial group (240 respondents) and the non-entrepreneurial group (202 respondents). Closed-ended questionnaire in “one score one indicator scoring” system pattern was provided to the respondents. Data were analysed in a quantitative descriptive manner based on the average value of each indicator. Analysis of causality between variables was conducted using logistic regression analysis. The results show that external factors that significantly affect rural ecotourism entrepreneurship are dominated by social aspects (seven factors) and some aspects of the entrepreneurship ecosystem, namely 1) market, 2) finance, and 3) business culture. The highest odds ratio is in the social interaction variable, 5.459, while the lowest is in the group solidarity variable, which is 0.323. With the odds ratio of social interaction of 5.459, it can be interpreted that if social interaction in the tourist village increases, it will tend to cause success in entrepreneurship 5.459 times higher than in the absence of social interaction. By utilising raw materials derived from natural resources, the ecotourism business will encourage business actors to be more concerned with preserving resources and forests and the environment. Therefore, entrepreneurship in the field of rural ecotourism must be optimally supported by all stakeholders involved.